Assessing the Increase of Snakebite Incidence in Relationship to Flooding Events. (18th May 2020) - Ochoa, Carlos; Bolon, Isabelle; Durso, Andrew M.; Ruiz de Castañeda, Rafael; Alcoba, Gabriel; Babo Martins, Sara; Chappuis, François; Ray, Nicolas
Abstract : Snakebite envenoming causes up to 138, 000 deaths and 400, 000 permanently disabled victims worldwide every year. Flooding is one of the many factors that seems to influence the incidence of snakebite. The catastrophic floods from late 2018 in Kerala (India) were widely broadcast and are an example of how flooding events are related to the increased incidence of snakebite. This relationship has been mentioned regularly in scientific and grey literature, but usually quite scarcely in comparison to other topics linked to snakebite. Additionally, web media, mobile communications, and social media have started playing an important role not only in providing access to information on flooding-related snakebite events, but also in snakebite prevention at a larger scale. In order to better understand to what extent the relationship between snakebite incidence and flooding is reported and quantified and appraise the importance of mobile communications and social media in snakebite prevention and management, we performed multiple searches in generic (Google) and specialized (PubMed, Web of Science, Google Scholar) databases. We retrieved 68 scientific articles and 5 reports ranging from 1892 to 2018 mentioning or analyzing flooding and the increased incidence of snakebite. Additionally, we found 68 web media reports linking flooding and snakebite. This review indicates that the increase of snakebite incidence due to flooding has been repeatedly observed all over the world. This phenomenon could be exacerbated because of climate change, which is expected to increase the overall magnitude and frequency of flooding. However, it could also be mitigated by the role the Internet, mobile communications, and social media could play in snakebite prevention and human and animal rescue strategies during flooding.